A composite phosphate positive electrode material and preparation method thereof
Through a simplified preparation method, a composite phosphate cathode material with a core-shell structure was prepared, which solved the problems of complex process and unstable performance in the prior art, and achieved efficient and excellent material preparation.
Patent Information
- Application Number
- CN202411378033.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-09-30
AI Technical Summary
The existing preparation methods for composite phosphate cathode materials have problems such as complex process, high cost, and unstable material performance, which limit their large-scale application.
A simple preparation method is adopted to mix manganese source, phosphorus source, lithium source and inorganic carbon source to prepare a lithium manganese phosphate core, and then mix the lithium manganese phosphate core with iron source, phosphorus source, lithium source and composite carbon source. It forms a composite phosphate positive electrode material, forming a core composed of lithium manganese phosphate and a shell composed of lithium iron phosphate. It has an Internet-shaped carbon material inside and a uniform carbon cladding layer outside.
Achieve efficient preparation of composite phosphate positive electrode material with unique core-shell structure. The inner core has high activity and good electronic conductivity. The outer shell improves cycling stability. The inner carbon material enhances conductivity. The outer carbon coating protects the material. It has improved electrochemical reactivity, excellent material performance, and has good practical value.
Smart Images

Figure CN118877860B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a composite phosphate positive electrode material and a preparation method thereof. Background Art
[0002] With the growth of energy demand and the increasingly severe environmental problems, the research and development of positive electrode materials of lithium-ion batteries as an important energy storage device has received extensive attention. At present, lithium iron phosphate (LiFePO4) occupies an important position in the market due to its good cycle performance and safety. However, the poor electronic conductivity of lithium iron phosphate limits its application in high-rate discharge occasions. On the other hand, although lithium manganese phosphate (LiMnPO4) has higher voltage and better electronic conductivity, its capacity and cycle performance still need to be further improved.
[0003] In order to overcome the limitations of a single material, researchers have tried to develop composite phosphate cathode materials to combine the advantages of different materials. However, existing composite phosphate cathode material preparation methods often have problems such as complex processes, high costs, and unstable material properties, which limit their large-scale application. Summary of the invention
[0004] The object of the present invention is to provide a composite phosphate positive electrode material and a preparation method thereof. The preparation method is simple to operate, has low requirements on equipment, and can efficiently prepare a composite phosphate positive electrode material with a unique core-shell structure.
[0005] The embodiment of the present invention is achieved as follows:
[0006] A method for preparing a composite phosphate positive electrode material, comprising:
[0007] Mixing a manganese source, a phosphorus source, a lithium source and an inorganic carbon source to form a first powder;
[0008] Sintering the first powder to obtain a lithium manganese phosphate core;
[0009] The lithium manganese phosphate core, the iron source, the phosphorus source, the lithium source, and the composite carbon source are mixed to form a second powder;
[0010] The second powder is sintered to obtain.
[0011] A composite phosphate positive electrode material is prepared by the above-mentioned composite phosphate positive electrode material preparation method; the composite phosphate positive electrode material comprises a core composed of lithium manganese phosphate and an outer shell composed of lithium iron phosphate, a network-shaped carbon material is formed inside, and a uniform carbon coating layer is formed outside.
[0012] The beneficial effects of the embodiments of the present invention are:
[0013] The embodiment of the present invention provides a composite phosphate positive electrode material and a preparation method thereof. The preparation method first mixes a manganese source, a phosphorus source, a lithium source and an inorganic carbon source to prepare a lithium manganese phosphate core, and then the lithium manganese phosphate core is made into a composite phosphate positive electrode material together with an iron source, a phosphorus source, a lithium source and a composite carbon source. The composite phosphate positive electrode material includes a core composed of lithium manganese phosphate and an outer shell composed of lithium iron phosphate, wherein a network-like carbon material is formed inside and a uniform carbon coating layer is provided outside. The lithium manganese phosphate of the inner core has high activity and better electronic conductivity; the lithium iron phosphate of the outer shell reduces manganese dissolution and improves the cycle stability of the material; the internal interconnected network carbon material enhances the internal conductivity and improves the rate performance of the material; the uniform and consistent carbon coating layer on the outside protects the material structure and improves the electrochemical reaction activity. The composite phosphate positive electrode material is easy to prepare, has excellent performance, and has good practical value. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0015] Figure 1 A schematic diagram of the structure of a composite phosphate positive electrode material provided in Example 1 of the present invention; wherein: 1- lithium manganese phosphate core, 2- lithium iron phosphate shell, 3- mesh carbon, 4- carbon coating layer;
[0016] Figure 2 This is a scanning electron microscope image of Example 1 of the present invention;
[0017] Figure 3 This is the electrochemical performance diagram of Example 1 of the present invention. DETAILED DESCRIPTION
[0018] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0019] A composite phosphate positive electrode material and a preparation method thereof according to an embodiment of the present invention are described in detail below.
[0020] An embodiment of the present invention provides a method for preparing a composite phosphate positive electrode material, which comprises:
[0021] S1. The manganese source, the phosphorus source, the lithium source and the inorganic carbon source are mixed and prepared into a first powder;
[0022] S2. The first powder is sintered to obtain a lithium manganese phosphate core;
[0023] S3. The lithium manganese phosphate core, an iron source, a phosphorus source, a lithium source, and a composite carbon source are mixed and prepared into a second powder;
[0024] S4. Sintering the second powder to obtain.
[0025] The manganese source includes at least one of manganese carbonate, manganese oxalate, manganese tetraoxide, manganese dioxide, manganese nitrate, manganese acetate, manganese phosphate and manganese sulfate; the phosphorus source includes at least one of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, lithium dihydrogen phosphate and phosphoric acid; the lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium dihydrogen phosphate and lithium acetate. The manganese source, phosphorus source and lithium source are all commercially available materials.
[0026] In the preparation of the first powder, each raw material is weighed according to the molar ratio of each element in LiMnPO4. Optionally, the molar ratio of Mn:P:Li provided by the manganese source, phosphorus source and lithium source is 0.99~1:0.98~1.01:0.98~1.01.
[0027] The inorganic carbon source includes at least one of carbon black, acetylene black and ammonium bicarbonate. The inorganic carbon source forms amorphous carbon or a simple crystalline structure during the carbonization process, has a more regular layered structure, and is more conducive to the rapid transfer of electrons. Optionally, in the first powder, the amount of the inorganic carbon source is 2wt%~8wt%. Within the above range, the inorganic carbon source can better form an interconnected network structure inside the composite phosphate positive electrode material.
[0028] Furthermore, the first powder is firstly ground to a median particle size of 0.1-0.2 μm, and then sintered. The grinding is performed in the form of wet grinding by a ball mill, and after grinding to a desired particle size, spray drying and granulation are performed.
[0029] In addition, the sintering of the first powder is carried out in an inert atmosphere, which is nitrogen or argon. The sintering temperature is 400~600℃, and the sintering time is 6~12 hours. Sintering under this condition can form a stable lithium manganese phosphate core and improve the overall performance. It should be noted that the sintering temperature of the first powder should not be too high. Too high a sintering temperature will cause the grains to stick together and fail to form a network carbon structure, resulting in a decrease in product performance.
[0030] Furthermore, the iron source includes at least one of ferric acetate, ferrous sulfate, ferrous nitrate, ferric nitrate, ferric sulfate, ferrous oxalate, ferrous oxide and ferric hydroxide. In actual operation, commercially available lithium iron phosphate powder can also be directly used to replace the iron source, phosphorus source and lithium source in the second powder. The molar ratio of Mn:Fe provided by the manganese source and the iron source is 1:0.6~0.7. Within the above ratio range, the overall performance of the material is better.
[0031] In the preparation of the second powder, each raw material is weighed according to the molar ratio of each element in LiFePO4. Optionally, the molar ratio of Fe:P:Li provided by the iron source, phosphorus source and lithium source is 0.99~1:0.98~1.01:0.98~1.01.
[0032] The composite carbon source is a mixture of an inorganic carbon source and an organic carbon source in a mass ratio of 1:8~10, and the organic carbon source includes at least one of glucose, sucrose, PEG-4000 and citric acid. The organic carbon source is easy to form a uniform and porous film structure during the carbonization process, which usually has a high porosity and complex structure, which is conducive to the rapid shuttling of ions. A small amount of inorganic carbon source is combined to improve the electron transfer performance, and a high-performance carbon coating layer can be obtained. In the second powder, the amount of the composite carbon source is 4wt%~10wt%. Within the above range, the thickness of the carbon coating layer is moderate, which can better maintain structural stability and reaction activity.
[0033] Similarly, during the preparation process, the second powder is first ground to a median particle size of 0.3-0.5 μm, and then sintered. The grinding is carried out in the form of wet grinding in a ball mill, and after grinding to the desired particle size, spray drying and granulation are performed. During the grinding process, the iron source, phosphorus source, lithium source, and composite carbon source will adhere to the surface of the lithium manganese phosphate core and finally sintered into shape.
[0034] Optionally, the second powder is sintered in an inert atmosphere at a sintering temperature of 600-800°C for 6-12 hours. Sintering under such conditions can promote the formation of the lithium iron phosphate surface layer and obtain a composite phosphate cathode material with excellent morphology and performance.
[0035] The embodiment of the present invention further provides a composite phosphate positive electrode material, which is prepared by the above-mentioned preparation method of the composite phosphate positive electrode material. Figure 1 As shown, the composite phosphate positive electrode material includes a lithium manganese phosphate core 1 composed of lithium manganese phosphate and a lithium iron phosphate shell 2 composed of lithium iron phosphate, wherein a network-like mesh carbon 3 is formed inside and a uniform carbon coating layer 4 is provided outside.
[0036] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0037] Example 1
[0038] This embodiment provides a composite phosphate positive electrode material, and the preparation method thereof is as follows:
[0039] S1. Manganese tetraoxide, lithium dihydrogen phosphate, and lithium carbonate (Mn:P:Li=1:1:1) were mixed, 6 wt% of carbon black was added, and the mixture was dispersed with water to form a slurry. The slurry was wet-milled until the median particle size reached 0.1-0.2 μm, and then spray-dried to obtain a first powder.
[0040] S2. The first powder is sintered in an inert atmosphere at a sintering temperature of 500° C. for 8 h to obtain a small particle lithium manganese phosphate core.
[0041] S3. The lithium manganese phosphate core in step S2 is mixed with iron phosphate, lithium dihydrogen phosphate, and lithium carbonate (Fe:P:Li = 1:1:1) to make the molar ratio of Mn:Fe be 1:0.67, and 8wt% of a composite carbon source (carbon black:sucrose = 1:9) is added, and the mixture is dispersed in water to form a slurry. The slurry is wet-milled to a median particle size of 0.3-0.5μm, and then spray-dried to obtain a second powder.
[0042] S4. The second powder is sintered in an inert atmosphere at a sintering temperature of 700° C. for 10 h to obtain a composite phosphate positive electrode material, lithium manganese iron phosphate.
[0043] Figure 2 This is a scanning electron microscope image of the composite phosphate positive electrode material. Figure 2 It can be seen that the composite phosphate positive electrode material has uniform particle size distribution, clear morphology, high sphericity, and obvious advantages in compaction and capacity. Figure 3 This is the electrochemical performance diagram of the composite phosphate positive electrode material. It can be seen that the capacity of the composite phosphate positive electrode material can reach 152 mAh / g at 0.1C, and it has better charge and discharge performance.
[0044] Example 2
[0045] This embodiment provides a composite phosphate positive electrode material, and the preparation method thereof is as follows:
[0046] S1. Manganese oxalate, ammonium dihydrogen phosphate, and lithium hydroxide (Mn: P: Li = 0.99: 1: 0.98) were mixed, 8 wt% of acetylene black was added, and the mixture was dispersed with water to form a slurry. The slurry was wet-milled until the median particle size reached 0.1-0.2 μm, and then spray-dried to obtain a first powder.
[0047] S2. The first powder is sintered in an inert atmosphere at a sintering temperature of 500° C. for 8 h to obtain a small particle lithium manganese phosphate core.
[0048] S3. The lithium manganese phosphate core in step S2 is mixed with ferric acetate, ammonium dihydrogen phosphate, and lithium hydroxide (Fe:P:Li = 0.99:1:1.01) to make the molar ratio of Mn:Fe be 1:0.6, and 10wt% of a composite carbon source (acetylene black: glucose = 1:8) is added, and the mixture is dispersed in water to form a slurry. The slurry is wet-milled to a median particle size of 0.3-0.5μm, and then spray-dried to obtain a second powder.
[0049] S4. The second powder is sintered in an inert atmosphere at a sintering temperature of 700° C. for 10 h to obtain a composite phosphate positive electrode material, lithium manganese iron phosphate.
[0050] Example 3
[0051] This embodiment provides a composite phosphate positive electrode material, and the preparation method thereof is as follows:
[0052] S1. Manganese nitrate, ammonium dihydrogen phosphate, and lithium acetate (Mn:P:Li=1:0.98:1) were mixed, 6 wt% of ammonium bicarbonate was added, and the mixture was dispersed with water to form a slurry. The slurry was wet-milled until the median particle size reached 0.1-0.2 μm, and then spray-dried to obtain a first powder.
[0053] S2. The first powder is sintered in an inert atmosphere at a sintering temperature of 400° C. for 8 h to obtain a small particle lithium manganese phosphate core.
[0054] S3. The lithium manganese phosphate core in step S2 is mixed with ferrous nitrate, ammonium dihydrogen phosphate, and lithium acetate (Fe:P:Li = 1:1:0.99) to make the molar ratio of Mn:Fe be 1:0.7, and 8wt% of a composite carbon source (ammonium bicarbonate: citric acid = 1:10) is added, and the mixture is dispersed with water to form a slurry. The slurry is wet-milled to a median particle size of 0.3-0.5μm, and then spray-dried to obtain a second powder.
[0055] S4. The second powder is sintered in an inert atmosphere at a sintering temperature of 600° C. for 10 h to obtain a composite phosphate positive electrode material, lithium manganese iron phosphate.
[0056] Example 4
[0057] This embodiment provides a composite phosphate positive electrode material, and the preparation method thereof is as follows:
[0058] S1. Manganese phosphate, phosphoric acid, and lithium carbonate (Mn:P:Li=1:1:1) are mixed, 4 wt% of carbon black is added, and the mixture is dispersed in water to form a slurry. The slurry is wet-milled until the median particle size reaches 0.1-0.2 μm, and then spray-dried to obtain a first powder.
[0059] S2. The first powder is sintered in an inert atmosphere at a sintering temperature of 550° C. for 8 h to obtain a small particle lithium manganese phosphate core.
[0060] S3. The lithium manganese phosphate core in step S2 is mixed with ferric oxide, lithium dihydrogen phosphate, and lithium carbonate (Fe:P:Li = 1:1:1) to make the molar ratio of Mn:Fe be 1:0.6~0.7, and 8wt% of a composite carbon source (acetylene black: glucose = 1:10) is added, and the mixture is dispersed in water to form a slurry. The slurry is wet-milled to a median particle size of 0.3~0.5μm, and then spray-dried to obtain a second powder.
[0061] S4. The second powder is sintered in an inert atmosphere at a sintering temperature of 750° C. for 10 h to obtain a composite phosphate positive electrode material, lithium manganese iron phosphate.
[0062] Comparative Example 1
[0063] This comparative example provides a composite phosphate positive electrode material, and the preparation method thereof is as follows:
[0064] S1. Manganese tetraoxide, lithium dihydrogen phosphate, and lithium carbonate (Mn:P:Li=1:1:1) were mixed, 6 wt% of carbon black was added, and the mixture was dispersed with water to form a slurry. The slurry was wet-milled until the median particle size reached 0.1-0.2 μm, and then spray-dried to obtain a first powder.
[0065] S2. The first powder is sintered in an inert atmosphere at a sintering temperature of 500° C. for 8 h to obtain small particles of lithium manganese phosphate.
[0066] S3. Mix iron phosphate, lithium dihydrogen phosphate, and lithium carbonate (Fe:P:Li = 1:1:1), add 8wt% of a composite carbon source (carbon black:sucrose = 1:9), and disperse with water to form a slurry. Wet-grind the slurry until the median particle size reaches 0.1-0.2μm, and then spray-dry to obtain a second powder.
[0067] S4. Sintering the second powder in an inert atmosphere at a sintering temperature of 700° C. for 10 h to obtain small particles of lithium iron phosphate.
[0068] S5. Mixing small particles of lithium manganese phosphate and small particles of lithium iron phosphate in a molar ratio of Mn:Fe of 1:0.67.
[0069] Comparative Example 2
[0070] This comparative example provides a composite phosphate positive electrode material, and its preparation method is basically the same as that of Example 1, except that the carbon black in step S1 is replaced by an equal amount of sucrose.
[0071] Comparative Example 3
[0072] This comparative example provides a composite phosphate positive electrode material, and its preparation method is basically the same as that of Example 1, except that the composite carbon source in step S3 is replaced by an equal amount of carbon black.
[0073] Comparative Example 4
[0074] This comparative example provides a composite phosphate positive electrode material, and its preparation method is basically the same as that of Example 1, except that the second powder in step S3 is ground to a median particle size of 0.1-0.2 μm.
[0075] Comparative Example 5
[0076] This comparative example provides a composite phosphate positive electrode material, and its preparation method is basically the same as that of Example 1, except that the sintering temperature in step S2 is increased to 650° C. and the sintering time is 12 h.
[0077] Test example
[0078] The composite phosphate positive electrode materials provided in Examples 1 to 4 and Comparative Examples 1 to 5 were used to test their carbon content, compaction density and discharge specific capacity, respectively. The test results are shown in Table 1.
[0079] Table 1. Test results of composite phosphate cathode materials
[0080] Carbon content (%) Compacted density (g / cc) 0.1C discharge specific capacity (mAh / g) Example 1 1.67 2.29 152.1 Example 2 1.75 2.24 150.1 Example 3 1.70 2.26 149.3 Example 4 1.64 2.25 146.3 Comparative Example 1 1.65 2.19 140.3 Comparative Example 2 1.67 2.20 139.5 Comparative Example 3 1.63 2.21 141.1 Comparative Example 4 1.68 2.18 134.7 Comparative Example 5 1.66 2.17 136.0
[0081] As can be seen from Table 1, the carbon content of the composite phosphate positive electrode material provided in the embodiment of the present invention reaches 1.63%~1.75%, the compaction density is 2.17~2.29g / cc, and the 0.1C discharge specific capacity reaches 152.1 mAh / g or more. In contrast, Comparative Example 1 simply physically mixes lithium iron phosphate and lithium manganese phosphate, and the 0.1C discharge specific capacity of the obtained product is far less than that of the embodiment of the present invention, reaching only 140.3mAh / g. Comparative Example 2 replaces the inorganic carbon source in the first powder with an organic carbon source. It is found that the organic carbon source forms a porous sheet-connected structure, and it is difficult to obtain the expected network structure, resulting in a significant decrease in discharge performance, reaching only 139.5mAh / g. Comparative Example 3 replaces the composite carbon source in the second powder with an inorganic carbon source, resulting in poor uniformity and stability of the carbon coating layer on the surface of the product, thereby affecting the discharge performance of the product, and its 0.1C discharge specific capacity only reaches 141.1mAh / g. In Comparative Example 4, the second powder was ground finer, and the iron source and other raw materials did not cover the lithium manganese phosphate core sufficiently, and the 0.1C discharge capacity of the final product reached 134.7 mAh / g, which was significantly lower than the result of the present invention. In Comparative Example 5, after the primary sintering temperature was increased and delayed, the lithium manganese phosphate core was severely adhered, which was because the high temperature caused the network structure to be damaged and the grains to adhere, and the 0.1C discharge capacity of the final product reached 136.0 mAh / g.
[0082] In summary, the embodiment of the present invention provides a composite phosphate positive electrode material and a preparation method thereof. The preparation method first mixes a manganese source, a phosphorus source, a lithium source and an inorganic carbon source to prepare a lithium manganese phosphate core, and then the lithium manganese phosphate core is made into a composite phosphate positive electrode material together with an iron source, a phosphorus source, a lithium source and a composite carbon source. The composite phosphate positive electrode material includes a core composed of lithium manganese phosphate and an outer shell composed of lithium iron phosphate, wherein a network-like carbon material is formed inside and a uniform carbon coating layer is provided outside. The lithium manganese phosphate of the inner core has high activity and better electronic conductivity; the lithium iron phosphate of the outer shell reduces manganese dissolution and improves the cycle stability of the material; the internal interconnected network carbon material enhances the internal conductivity and improves the rate performance of the material; the uniform and consistent carbon coating layer on the outside protects the material structure and improves the electrochemical reaction activity. The composite phosphate positive electrode material is easy to prepare, has excellent performance, and has good practical value.
[0083] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a composite phosphate positive electrode material, characterized in that: include: Mixing a manganese source, a phosphorus source, a lithium source and an inorganic carbon source to form a first powder; Sintering the first powder to obtain a lithium manganese phosphate core; The lithium manganese phosphate core, the iron source, the phosphorus source, the lithium source, and the composite carbon source are mixed to form a second powder; The second powder is sintered to obtain; The inorganic carbon source includes at least one of carbon black, acetylene black and ammonium bicarbonate; in the first powder, the amount of the inorganic carbon source is 2wt% to 8wt%; The composite carbon source is formed by mixing the inorganic carbon source and the organic carbon source in a mass ratio of 1:8-10, and the organic carbon source includes at least one of glucose, sucrose, PEG-4000 and citric acid; in the second powder, the amount of the composite carbon source is 4wt%-10wt%.
2. The preparation method according to claim 1, characterized in that: The manganese source includes at least one of manganese carbonate, manganese oxalate, manganese tetraoxide, manganese dioxide, manganese nitrate, manganese acetate, manganese phosphate and manganese sulfate; the phosphorus source includes at least one of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, lithium dihydrogen phosphate and phosphoric acid; the lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium dihydrogen phosphate and lithium acetate.
3. The preparation method according to claim 1, characterized in that: The first powder is ground to a median particle size of 0.1-0.2 μm, and then sintered.
4. The preparation method according to claim 1, characterized in that: The sintering of the first powder is carried out in an inert atmosphere, the sintering temperature is 400-600° C., and the sintering time is 6-12 h.
5. The preparation method according to claim 1, characterized in that: The iron source includes at least one of ferric acetate, ferrous sulfate, ferrous nitrate, ferric nitrate, ferric sulfate, ferrous oxalate, ferrous oxide and ferric hydroxide; the molar ratio of Mn:Fe provided by the manganese source and the iron source is 1:0.6~0.
7.
6. The preparation method according to claim 1, characterized in that: The second powder is ground to a median particle size of 0.3-0.5 μm, and then sintered.
7. The preparation method according to claim 1, characterized in that: The sintering of the second powder is carried out in an inert atmosphere, the sintering temperature is 600-800° C., and the sintering time is 6-12 h.
8. A composite phosphate positive electrode material, characterized in that: The composite phosphate positive electrode material is prepared by the preparation method of the composite phosphate positive electrode material as described in any one of claims 1 to 7; the composite phosphate positive electrode material comprises a core composed of lithium manganese phosphate and an outer shell composed of lithium iron phosphate, a network-shaped carbon material is formed inside, and a uniform carbon coating layer is formed outside.
Citation Information
Patent Citations
Carbon coated lithium manganese phosphate / lithium iron phosphate core-shell structure material as well as preparation method thereof
CN103515594A
Composite battery positive electrode material, preparation method and battery
CN117542971A